FRI0267 Mycophenolate Mofetil versus Oral Cyclophosphamide in Scleroderma-Related Interstitial Lung Disease: Scleroderma Lung Study II. (15th July 2016) - Khanna, D.; Roth, M.; Clements, P.; Furst, D.; Tseng, C.-H.; Elashoff, R.; Volkmann, E.; Kafaja, S.; Goldin, J.; Tashkin, D.; ,
Abstract : Background: Progressive Interstitial lung disease (ILD) occurs in ∼ 40% of scleroderma (SSc) patients and is the leading cause of death. Oral CYC for 1 year in SSc-ILD led to modest but significant improvements in lung function and dyspnea vs. placebo (Tashkin, NEJM, 2006) but the benefits were lost over the ensuing year and drug therapy was not extended due to the known toxicity profile of CYC. (Tashkin AJRCCM 2007). Preliminary data from uncontrolled clinical studies suggest that MMF may be an effective and safer immunosuppressive therapy than CYC for SSc-ILD. Objectives: A randomized controlled trial was performed to determine the efficacy, safety and tolerability of mycophenolate mofetil (MMF) administered for two years compared with CYC administered for one year followed by matching placebo for SSc-ILD. Methods: 142 patients with pulmonary function and high-resolution computed tomography (HRCT) defined SSc-ILD were randomized at 14 centers to receive MMF or CYC. The primary endpoint, change in forced vital capacity (FVC%>predicted) over 24 months, was assessed using a joint longitudinal model (Elashoff, Statist Med 2006). Results: 126 patients (63 MMF; 63 CYC) had ≥3 months of outcome data and were included in the primary analysis. A greater number of patients on CYC than on MMF prematurely withdrew from (32 vs 20) and failed treatment (2 vs 0), and the time to stopping treatment was significantly shorter in the CYC arm (p=0.019). At 24-months, the adjusted FVC%>predicted had improved by 2.17 in the MMF arm (95% CI, 0.53–3.84; p<0.01) and 2.86 in the CYC arm (95% confidence interval 1.19–4.58; p<0.001) with no significant between-treatment difference (p=0.24). Significant within- (but not between-) treatment improvements in skin score, dyspnea and whole-lung HRCT scores were also observed. Leukopenia and thrombocytopenia occurred more often with CYC (p<0.05). Sixteen deaths occurred (11 CYC; 5 MMF) with most due to underlying disease. Conclusions: In this first RCT comparing MMF with CYC in SSc-ILD, both agents appeared to have comparable efficacy but MMF was better tolerated with significantly fewer premature withdrawals from treatment and fewer adverse events. These findings support the increasingly common clinical practice of prescribing MMF for this disease. Acknowledgement: Funded by the National Heart, Lung, and Blood Institute, National Institutes of Health; ClinicalTrials.gov number NCT00883129 . Disclosure of Interest: None declared